Promising strategies in natural products treatments of psoriasis-update - Le, Sihua; Wu, Xuan; Dou, Yuan; Song, Tianhao; Fu, Hongyang; Luo, Hongbin; Zhang, Fan; Cao, Yi (Frontiers in Medicine, 2024)
Psoriasis is a chronic, relapsing, inflammatory skin disease and has been increasing year by year.It is linked to other serious illnesses, such as psoriatic arthritis, cardiometabolic syndrome, and depression, resulting in a notable decrease in the quality of life for patients. Existing therapies merely alleviate symptoms, rather than providing a cure. An in-depth under-standing of the pathogenesis of psoriasis is helpful to discover new therapeutic targets and develop effective novel therapeutic agents, so it has important clinical significance. This article reviews the new progress in the study of pathogenesis and natural products of psoriasis in recent years. These natural products were summarized, mainly classified as terpenoids, polyphenols and alkaloids. However, the translation of experimental results to the clinic takes a long way to go.